Carnitine Palmitoyl Tranferase Type 1 Deficiency in Fatty acid oxidation disorder: A Case report (Journal of Shaheed Suhrawardy Medical College, 2017)
Carnitine palmitoyltransferase 1(CPT-1) catalyzes the formation of acylcarnitine, which is the first step in the oxidation of long chain fatty acid in the mitochondria. CPT-1 deficiency is an inborn error of metabolism. Reported patient with CPT -1 deficiency was a 16 months old boy present with hypoketotic hypoglycaemia, hepatomegaly with raised liver transaminases, hyperamminaemia, convulsion and unconsciousness. Diagnosis was established by IMD panel study. Treatment was done by correction of hypoglycemia, avoidance of hypoglycemia by ensuring frequent feeding, avoidance of prolonged fasting, treatment of infection & other supportive measures.J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 38-40